STUDYING THE CONDITIONS AND SOLVING PROBLEMS OF THE SCHOOL GEOMETRY COURSE - Seitbekova , Г.; Kokazhaeva , А.; Omurzhakova , Г. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article tells about the relevance of the process of studying the conditions and solving problems of the school course of geometry and the practical importance of the correct formation of students' thinking skills in the modern education system. The article discusses the main feature of solving geometric problems - the need to form the student's skills of realizing the correctness or incorrectness of the condition of its transfer, paying attention to the representation of the problem. Due to the ability to clearly and correctly solve problems of the school course of geometry, students quickly develop skills of logical thinking, conceptual thinking. Due to incorrect or incomplete presentation of the text of geometry problems, the vast majority of students during UNT received results below the number of test questions, an example of which is several test problems with the reasons for uncertainties. The article analyzes the most important cases when school geometry courses do not provide a complete and correct description of a problem and concludes with a brief guide to prevent such gaps in the future.